1998
DOI: 10.1002/(sici)1096-8628(19980923)79:3<205::aid-ajmg11>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Smith-Fineman-Myers syndrome in apparently monozygotic twins

Abstract: We report on two boys, monozygotic twins born to normal and nonconsanguineous parents, presenting with an unusual facial appearance, cortical atrophy, dolichocephaly, short stature, cleft palate, micrognathia, prominent upper central incisors, bilateral Sidney line, minor foot deformities, unstableness in walking, early hypotonia, hyperreflexia, hyperactivity, psychomotor retardation, and severe delay in language development. These manifestations resemble those previously described in the Smith-Fineman-Myers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…It is by no means certain that all reports of Smith–Fineman–Myers syndrome reported, to date, share the same underlying genetic entity. [Smith et al, 1980; Stephenson and Johnson, 1985; Adès et al, 1991; Wei et al, 1993; Guion‐Almeida et al, 1998]. As with our own patient, Adès et al [1991] observed Howell–Jolly bodies in the peripheral blood film of Case 1 of that report, leading to a diagnosis of congenital asplenia.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It is by no means certain that all reports of Smith–Fineman–Myers syndrome reported, to date, share the same underlying genetic entity. [Smith et al, 1980; Stephenson and Johnson, 1985; Adès et al, 1991; Wei et al, 1993; Guion‐Almeida et al, 1998]. As with our own patient, Adès et al [1991] observed Howell–Jolly bodies in the peripheral blood film of Case 1 of that report, leading to a diagnosis of congenital asplenia.…”
Section: Discussionsupporting
confidence: 67%
“…The entity known as Smith–Fineman–Myers syndrome stems from the 1980 report of brothers with mental retardation, seizures, neurological dysfunction, and short stature [Smith et al, 1980]. Subsequent cases considered to have the same disorder have been reported by Stephenson and Johnson [1985], Wei et al [1993], Guion‐Almeida et al [1998], and Adès et al [1991]. In general, the facial features of subjects reported have not been noteworthy, with the exception of the Ades et al report.…”
Section: Introductionmentioning
confidence: 99%
“…It is by no means certain that all reports of Smith-Fineman-Myers syndrome reported, to date, share the same underlying genetic entity. [Smith et al, 1980;Stephenson and Johnson, 1985;Adès et al, 1991;Wei et al, 1993;Guion-Almeida et al, 1998]. As with our own patient, Adès et al [1991] observed Howell-Jolly bodies in the peripheral blood film of Case 1 of that report, leading to a diagnosis of congenital asplenia.…”
Section: Discussionsupporting
confidence: 60%
“…The entity known as Smith-Fineman-Myers syndrome stems from the 1980 report of brothers with mental retardation, seizures, neurological dysfunction, and short stature [Smith et al, 1980]. Subsequent cases considered to have the same disorder have been reported by Stephenson and Johnson [1985], Wei et al [1993], Guion-Almeida et al [1998], and Adès et al [1991]. In general, the facial features of subjects reported have not been noteworthy, with the exception of the Ades et al report.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Patients reported as having Smith-Fineman-Myers indeed harbored a mutation in the XNP gene. 35 Finally, it appears that also the Chudley-Lowry syndrome (309490) results from a null mutation of the XNP gene.…”
Section: Xnp (X-linked Nuclear Protein) Genementioning
confidence: 99%